When Heroes Love: The Ambiguity of Eros in the Stories of Gilgamesh and David. Edited by Susan Ackerman. Pp. xvi + 353. New York: Columbia University Press, 2005. isbn 0 231 13260 3. 45/£29.50 - Guest, Deryn (The journal of theological studies, 2006)
The similarity of emotionally charged language and images of physical intimacy in the Gilgamesh Epic and the Samuel narratives relating to David and Jonathan has long been noted. What one is to make of these similarities and how one should best interpret the homoerotically charged narratives remains, however, subject to considerable debate. Moreover, contemporary interest in David and Jonathan as biblical ‘ancestors’ for contemporary gay men complicates and fuels that debate. Indeed, Ackerman acknowledges how her own interest in this study was partially motivated by the role that the Bible continues to play in political debates concerning the ‘place of gay men and lesbians within contemporary society’ (p. 2).